Floating culture: the unrecorded antiquities of England and Wales. Issue 9 (21st October 2017) - Daubney, Adam
Abstract: In England and Wales there exists a corpus of unprovenanced and unrecorded antiquities; a corpus adrift from archaeological context and now ebbing and flowing across the antiquities market and which could be described as 'floating culture'. This corpus includes illicit antiquities and also antiquities found legitimately but not recorded and subsequently sold with or without the landowner's knowledge. The definition of floating culture as 'traces of the human past not fixed on one position, place or level' presents a way of conceptualising what is, in essence, a transnational issue. This paper explores floating culture and suggests that the impact of non-reporting of antiquities remains a significant ethical and legal challenge both for heritage protection policy and the antiquities market in the U.K. and beyond. Attention is given to the Code of Practice for Responsible Metal Detecting in England and Wales, and to the landowner-finder search agreement as potential ways of mitigating the flow of unrecorded antiquities of uncertain legal status. While neither document is enforceable, both have potential to improve the protection of the archaeological record. Many of the themes conceptualised by 'floating culture' are relevant to the wider discussion on heritage protection and the global trade in illicit antiquities.